Minimally invasive aortic valve replacement through a transverse sternotomy: a word of caution. Issue 6 (1st June 1998) - Bridgewater, B; Steyn, R S; Ray, S; Hooper, T
Abstract : Objectives: To compare aortic valve replacement (AVR) using a minimally invasive approach through a transverse sternotomy with the established approach of median sternotomy. Design: Retrospective, case-control study. Patients: Fourteen high risk patients (median age 78, Parsonnet score of 18%) who underwent AVR performed through a minimally invasive transverse sternotomy were compared with a historical group of patients matched for age, sex, and Parsonnet score who underwent AVR performed through a median sternotomy by the same surgeon. Outcome measures: Cross clamp time, total bypass time, intensive care stay, postoperative in-hospital stay, morbidity, and mortality. Results: There were two deaths in the minimally invasive group and none in the control group (NS). The cross clamp and total bypass times were longer in the minimally invasive group (67 and 92 minutes v 46 and 66 minutes, p < 0.001). There was a higher incidence of re-exploration for bleeding (14% v 0%) and paravalvar leaks (21% v 0%) in the minimally invasive group but these differences were not significant. The minimally invasive group had a longer postoperative in-hospital stay (p = 0.025). The incidence of mortality or major morbidity was 43% (six of 14) in the minimally invasive group and 7% (one of 14) in the matched pairs (p = 0.013). Conclusions: AVR can be performed through a transverse sternotomy but the operation takes longer and there is an unacceptably high incidence of morbidity and mortality.